Survey of Dental Caries, Gingivitis Prevalence, Dietary, and Oral Hygiene Habits among Patients Visiting Dental Clinic in Zawia, Libya - Lubna S.Abdalrahman (Surman Journal of Science and Technology, 2022)
This study aims to estimate the predominance of tooth decay, periodontal disease, and dietary and oral hygiene practices among patients attending four dental clinics in Zawia, Libya, to determine the need for dental treatment. A total of 150 people were investigated (52 men and 98 females). To establish the patients' food and dental hygiene habits, interviews were done using a pre-determined questionnaire. The survey looked at dental knowledge, dental knowledge sources, and oral health behavior (e.g., daily frequency of tooth brushing, use of dental floss, and regular dental checkups). 100 percent of the males and females evaluated had caries that had been clinically diagnosed. Gingivitis was found in 75 percent of the men and 66.3 percent of the women who were tested. The findings imply that females are more likely than males to be free of gingivitis. Oral hygiene habits, such as teeth brushing frequency, were developed in 81 out of 98 females and 44 out of 52 men. 41 Females consume sweets/candy and soft drinks (every day) more than men. According to the findings, all of the patients in the four clinics had significant caries prevalence and treatment needs. As a result, there is a considerable demand for dental care and preventative measures. The dental clinic was the most prevalent source of dental information among the patients at Zawia. Libya and it was linked to better oral health behavior.